Sir William Wilson Hunter, Bengal MS Records : A Selected List of 14,136 Letters in the Board of Revenue, Calcutta, 1782-1807, with an Historical Dissertation and Analytical Index (Volumes I-IV 1782-1807) - Bhattacharyya, Ananda, (Brill | Manohar Publishers & Distributors, 2018)
W.W. Hunter's Bengal Ms Records 1782-1807 in four volumes, is based on the Collectorate records and the records of the Board of Revenue which were widely scattered. Hunter made an extensive survey of these records which are now available in a complete form in the record room of the Directorate of State Archives, West Bengal. The records relate to the judicial, civil, military and land revenue administration of the East India Company. The introductory note of Hunter as found in the Bengal Ms Records and the bulk of letters, throw light on the revenue work that progressed territorially with the expansion of the Presidency. The importance of the Board of Revenue records was given considerable significance as these records were the raw data for reconstructing these volumes. Hunter's omnibus compilation had thrown light on various districts of Bengal Presidency, viz.,Midnapore, Bissenpore (Bishnupur), Cuttuck, Rangpur, Dinajpur, Rajshahi, Mymensingh, Chittagong, Purneah, Bhagalpur, Shahabad and Benares and dealt with such matters as rent suits, waste lands, lakhiraj lands, Government estates and their settlements, customs, excise, salt, opium, indigo, police, post office, and public works including sanitation, embankments, stamps and survey. The consolidated index prepared by Hunter shows the exhaustive nature of his research and would prove to be a lodestone for scholars of colonialism in South Asia.